Body dysmorphia in common skin diseases: results of an observational, cross‐sectional multicentre study among dermatological outpatients in 17 European countries. (22nd May 2022) - Schut, Christina; Dalgard, Florence J.; Bewley, Anthony; Evers, Andrea W.M.; Gieler, Uwe; Lien, Lars; Sampogna, Francesca; Ständer, Sonja; Tomás‐Aragonés, Lucía; Vulink, Nienke; Finlay, Andrew Y.; Legat, Franz J.; et al.
Summary: Background: Body dysmorphic disorder (BDD) is a common psychiatric disorder associated with high costs for healthcare systems as patients may repeatedly ask for different, often not effective, interventions. BDD symptoms are more prevalent in patients with dermatological conditions than in the general population, but there are no large sample studies comparing the prevalence of BDD symptoms between patients with dermatological conditions and healthy skin controls. Objectives: To compare the prevalence of BDD symptoms between patients with different dermatological conditions and healthy skin controls and to describe sociodemographic, physical and psychological factors associated with BDD symptoms to identify patients who may have a particularly high chance of having this condition. Methods: This observational, cross‐sectional, comparative multicentre study included 8295 participants: 5487 consecutive patients with different skin diseases (56% female) recruited among dermatological outpatients at 22 clinics in 17 European countries, and 2808 healthy skin controls (66% female). BDD symptoms were assessed by the Dysmorphic Concern Questionnaire. Sociodemographic data and information on psychological factors and physical conditions were collected. Each patient was given a dermatological diagnosis according to ICD‐10 by a dermatologist. The study was registered with number DRKS00012745. Results: The average participation rate of invited dermatological patients was 82.4% across all centres. BDD symptoms were five times more prevalent in patients with dermatological conditions than in healthy skin controls (10.5% vs. 2.1%). Patients with hyperhidrosis, alopecia and vitiligo had a more than 11‐fold increased chance (adjusted Odds Ratio (OR) > 11) of having BDD symptoms compared with healthy skin controls, and patients with atopic dermatitis, psoriasis, acne, hidradenitis suppurativa, prurigo and bullous diseases had a more than sixfold increased chance (adjusted OR > 6) of having BDD symptoms. Using a logistic regression model, BDD symptoms were significantly related to lower age, female sex, higher psychological stress and feelings of stigmatization. Conclusions: Clinical BDD symptoms are significantly associated with common dermatological diseases. As such symptoms are associated with higher levels of psychological distress and multiple unhelpful consultations, general practitioners and dermatologists should consider BDD and refer patients when identified to an appropriate service for BDD screening and management. Abstract : What is already known about this topic? Body dysmorphic disorder (BDD) is a common psychiatric disorder with a prevalence of about 2% in the general population. Skin diseases pose a high psychological burden on patients. People with these problems often experience increased self‐consciousness, skin‐related shame and stigmatization. Single‐centre studies including small samples of patients with skin conditions showed that these patients show symptoms of a similar nature to BDD more often than the general population. What does this study add? In this large multicentre study, BDD symptoms were fivefold more prevalent in dermatological patients than in healthy skin controls, and were related to young age, female sex, psychological stress and stigmatization experience. Certain patient groups (e.g. hyperhidrosis) had a greater than 11‐fold increased chance of BDD symptoms compared with controls. Doctors should consider appearance‐related concern and BDD more often and refer patients when needed to an appropriate service for assessment and treatment. Body dysmorphic disorder (BDD) is a psychiatric condition affecting about 2.5 % of the general population. Patients with this condition are preoccupied with negative thoughts about their own appearance which highly impair their daily functioning. Skin diseases can pose a high psychological burden on patients partly due to visible skin lesions. BDD has been shown to affect dermatological patients quite often, but there are no large studies that include both patients with different dermatological conditions and healthy skin controls. This study included 8295 participants: 5487 patients with different skin diseases (56% female) recruited among dermatological out‐patients at 22 clinics in 17 European countries and 2808 people with healthy skin (66% female). Symptoms of BDD were measured using a self‐report questionnaire. In addition, each patient was given a dermatological diagnosis by a dermatologist. It was shown that BDD symptoms were five times more prevalent in patients with dermatological conditions than in people with healthy skin (10.5% vs. 2.1%). Certain dermatological patients (e.g. with excessive sweating, circular hairloss and white spot disease) had a more than eleven‐fold increased chance of BDD symptoms compared to people with healthy skin. It was also shown that BDD symptoms more often occurred in younger and in female persons, and those experiencing higher psychological stress and feeling stigmatized. As BDD symptoms are so common in dermatological patients, general practitioners and dermatologists should consider both BDD and appearance related distress and refer patients when identified to an appropriate service for further assessment and management. Linked Comment: P. Magin and K. Fisher. Br J Dermatol 2022; 187:5 . Plain language summary available online